Misdemeanor of Corruption within the Scope of International Law and the Legal Consequences - Arifin, Ridwan; Faridah, Siti; Naefi, Mohammad (JILS (Journal of Indonesian Legal Studies), 2019)
Corruption is a threat to stability, national and international security, institutions, democracy, justice and endangering sustainable development and law enforcement. In an international perspective, corruption is classified into white-collar crime as a crime that occurs in government institutions. The paper analyses the corruption in the international law perspective. The paper is intended to examine more deep concerning to corruption in the global perspective and international law, and how are consequences into domestic law. The method used for analytical study of this paper by analyze some related theories concerning to corruption in international law perspective. The paper highlighted and underlined that corruption in the global context can be prevented by international cooperation and collaboration in many forms, one of is regional or bilateral agreement on combating corruption.